A TEXTURA E A MOVIMENTAÇÃO DO FÓSFORO PROVENIENTE DO FOSFATO MONOAMÔNICO - LOPES, Fernando de Souza; ROSSI, Ana Carolina Marinho; PEROBELLI, Bruno de Oliveira; KUSANO, Daniel Makoto; ALVES CORRÊA, Marli Aparecida de Oliveira; CAMACHO, Marcos Antonio (ANAIS DO ENIC, 2018)
-